The Influence Of Digitalization, Bank Specifications, And Macroeconomics On Indonesia’s Bank Performance - Kurnia Yuniarti; Nurul Inayah; Fibby Luthfia; Henny Setyo Lestari (Jurnal Ekonomi, 2024)
This research aims to determine and analyse the effect of digitalisation, bank specifications, and macroeconomics on the performance of banks listed on the Indonesia Stock Exchange in the 2018-2022 period. Independent variables in this study include digitalisation, bank size, capital adequacy ratio, loan-to-asset ratio, loan-to-deposit ratio, nonperforming loans, Inflation, and gross domestic product. The dependent variable is financial performance measured using Return on Assets and Return on Equity. To analyse the data, this study uses the Eviews 12 program to analyse multiple linear regression. The study's results indicate that digitalisation, bank size, capital adequacy ratio, and loan-to-deposit ratio positively and significantly affect financial performance. Meanwhile, loan-to-asset ratios and nonperforming loans negatively and significantly affect a bank's financial performance. In contrast, Inflation and gross domestic product do not affect bank financial performance.